Dendrimer-based nanocomposites for the production of RNA delivery systems - Chiou Chyi Lim; Le Yi Chia; Palanirajan Vijayaraj Kumar (Elsevier, 2023)
A novel approach to treating cancer has been revealed to be effective cancer vaccination. It has also been demonstrated that nucleic acid therapies such as mRNA and siRNA are very efficient in the treatment of cancer. However, the instability of mRNA makes a delivery system necessary to reach the target sites. Dendrimers have emerged as being of important interest in healthcare due to their ideal characteristic of having a very strong drug delivery capacity to become carriers. The dendrimer's center can be loaded with specific pharmaceutical active ingredients, or they can be bonded to the surface. RNA delivery systems that transport siRNA, mRNA, and other forms of RNA can be made using dendrimers. This review article focuses on several dendrimer-based RNA delivery systems, such as dendrimers modified with PEG, mannosylated dendrimers, dendrisomes, amphiphilic dendrimer vectors, magnetic nanoparticles modified with dendrimers, peptide dendrimers, and gold nanoparticles coated with dendrimers.